Analisis Pelanggaran Etika Periklanan Pada Iklan Candi Borobudur di Media Sosial Tiktok - Muhammad Rizqullah Ramadhon; Fathan Ananta Hirzi; Pantja Putra Pandawa; Daniel Handoko (Indo Publishing, 2025)
Social media has become one of the main media for distributing various advertising content in today's digital era. However, the spread of advertising content on social media also brings new challenges. Social media, especially TikTok, has a high virality rate, which means that content can spread quickly, both positively and negatively. The TikTok account @ngobrolsantaiindonesia uploaded a promotional advertisement for Borobudur Temple. The entire narrative in the advertising content openly alludes to other religions, namely Islam. This study uses a research approach in the form of a literature study or can be called library research. Indonesia has guidelines that must be respected, namely the Indonesian Advertising Ethics or abbreviated as EPI. The EPI contains a system of values and integrated guidelines for manners (code of conducts) and procedures (code of practices) that apply to all advertising actors in Indonesia. According to the Indonesian Advertising Ethics, advertisements must be honest, correct, and responsible. It was concluded that the violation committed by the TikTok account @ngobrolsantaiindonesia was offending SARA, more specifically other religions.